Harrison's hematology and oncology - Longo, Dan L. (Dan Louis) (McGraw-Hill Education/Medical, 2013)
Featuring a compilation of chapters on hematology and oncology that appear in Harrison's Principles of Internal Medicine, Eighteenth Edition, this concise, full-color clinical companion delivers the latest knowledge in the field backed by the scientific rigor and authority that have defined Harrison's. You will find content from renowned editors and contributors in a carry-anywhere presentation that is ideal for the classroom, clinic, ward, or exam/certification preparation. Features: Organized into twelve sections: The Cellular Basis of Hematopoiesis; Cardinal Manifestations of Hematologic Diseases; Anemias, Myeloproliferative Disorders; Hematologic Malignancies; Disorders of Hemostasis; Biology of Cancer; Principles of Cancer Prevention and Treatment; Neoplastic Disorders; Endocrine Neoplasia; Remote Effects of Cancer; and Oncologic Emergencies and Late Effects Complications. Each chapter contents relevant information on the genetics, cell biology, pathophysiology, and treatment of specific disease entities. Chapters on hematopoiesis, cancer cell biology, and cancer prevention reflect the rapidly growing body of knowledge in these areas. Integration of pathophysiology with clinical management. 153 high-yield questions and answers drawn from Harrison's Principles of Internal Medicine Self-Assessment and Board Review, 18 edition. Content updates and new developments since the publication of Harrison's Principles of Internal Medicine, 18 edition, 55 chapters written by physicians who are recognized experts in the field of hematology and oncology. Helpful appendix of laboratory values of clinical importance.